Structural and Magnetic Properties of (1-x)Ba5PrTi3V7O30-xBiFeO3 - Doley, Hage (International Journal of Advanced Science Computing and Engineering, 2022)
Bismuth Ferrite (BiFeO3) is a single phase Fe- based multiferroic having Perovskite structure. It shows both ferroelectric and ferromagnetism simultaneously in the single material. But the magnetic order is very low due to complex antiferromagnetic order yielding small remnant magnetization. However, Magnetic property could be improved if BiFeO3 mixed with Ba5PrTi3V7O30 having TB-structure. Solid Solution (1-x)Ba5PrTi3V7O30-xBiFeO3 is prepared by using Solid State Reaction technique for different values of x. Pellets are calcined at 750  then sintered at 800 . Basic Crystal qualities and formation of single phase compound is confirmed by the XRD (X-Ray Diffractogram). The crystal structure is more or less constant i.e. Orthorhombic.  However, further increase in x changes the crystal structure. For x= 0.7 the system is Rhombohedral in structure. Grain morphology is being analysed by Scanning Electron Microscope (SEM: JOEL-IT300).Surface morphology shows that average grain size range from around 0.75 µm to 2.10 µm. Average grain size is maximum for x = 0.3 and minimum for x=0 (i.e. pure ferroelectric material). Magnetic measurement is done at a wide low temperature range (10-350K) by Physical Property Measurement System (PPMS: Quantum Design, San Diego, USA) Vibrating Sample Magnetometer (VSM). Hysteresis (M-H) loops are measured at room temperature (300K).It shows that the magnetization changes when the value of x changes. Remanence is maximum for x=0.3 and Coercivity is maximum for x=0.7. The material could be suitable to fabricate non volatile magnetic storage memory device.